Topics in public administration perspectives from computational social sciences and corpus linguistics - Walker, Richard M. (Cambridge University Press, 2024)
This inductive examination of the topics in the public administration literature using computational social science and corpus linguistics (17 journals, N=12,760 articles, 1991-2019) reveals a new landscape of public administration topics, changes in topics over time and their distribution: * Topic modelling of the stock of the whole corpus identifies 50 topics: the top ten topics included health care, federal government, performance management, environmental regulation, HRM and networks and accounted for just over a third of scholarship between 1991-2019. * Focal topics identified in individual journals identified similarities with popular topics in the whole corpus - networks, health care, HRM - and less frequently examined topics including gender and diversity and partnerships. * Analysis of topics over time shows a substantial flow in topics moving from a country and practice focus in the early stages of our study period to concepts such as governance, networks and citizens in the late stages (2015-2019).